2016
DOI: 10.1002/dneu.22404
|View full text |Cite
|
Sign up to set email alerts
|

Blocking elevated VEGF‐A attenuates non‐vasculature Fragile X syndrome abnormalities

Abstract: Fragile X syndrome (FXS) is the most common form of inherited mental retardation. In exploring abnormalities associated with the syndrome, we have recently demonstrated abnormal vascular density in a FXS mouse model (Galvan and Galvez, ). One of the most prominent regulators of vascular growth is VEGF-A (Vascular Endothelial Growth Factor A), suggesting that FXS is associated with abnormal VEGF-A expression. In addition to its role in vascular regulation, VEGF-A also induces cellular changes such as increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 54 publications
3
11
0
1
Order By: Relevance
“…Consistent with our prior studies in young adults (Galvan and Galvez, ; Belagodu et al, ), the current study found that PND 60 FXS mice had significantly elevated BVD and VEGF‐A expression (Figs. , and d).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with our prior studies in young adults (Galvan and Galvez, ; Belagodu et al, ), the current study found that PND 60 FXS mice had significantly elevated BVD and VEGF‐A expression (Figs. , and d).…”
Section: Discussionsupporting
confidence: 92%
“…Our prior studies have demonstrated that FXS is associated with adult abnormalities in both vascular density and VEGF‐A expression (Galvan and Galvez, ; Belagodu et al, ). More importantly, we have shown that decreasing VEGF‐A to WT levels can alleviate some FXS abnormalities (Belagodu et al, ). However, FXS is a developmental disorder and there are multiple VEGF proteins and receptors that could mediate FXS abnormalities at these developmental time points.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…To determine SHANK1 expression levels in the astrocyte‐enriched fraction, the sample along with a whole brain control was processed as described in (Belagodu et al, ). Briefly, cellular fractions were lysed and protein concentrations estimated via bicinchonic acid assay (Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%